±270 VDC Aircraft Harness Structural Analysis. (2015) - Sparr, Holger; Hausdorf, Alexander; Jeske, Peter; Kale, Nachiket; Schacht, Ralph; Ziegenhorn, Matthias; Zysk, Oliver
Abstract: This research focuses on the structural analysis of aircraft electrical harnesses for the 270 VDC network. A combined experimental and simulation-based approach is used, where numerical models for the harnesses are developed and experimental data are acquired for basic test cases (steady load, pendulum test, etc.) as well as for different vibration load cases. Validation of the numerical models is done using the preliminary experimental data, resulting in a mature refined model in order to simulate complex scenarios. The goal of the project is thus to develop a suite of tools that allows detailed structural analysis of the aircraft harnesses, both stand alone as well as in combination with other systems.